Relationship between sustainability reporting and firm's value: Evidence from Vietnam - Nguyen Van Linh; Dang Ngoc Hung; Ta Quang Binh (Cogent Business & Management, 2022)
Recent sustainability reporting (SR) has been of particular interest to stakeholders in developed countries but has begun to be studied in developing countries. The purpose of this study is to examine the relationship between SR and firm value (FV) of non-financial firms listed on the Vietnamese stock exchange. The authors used the combined method to measure the level of SR disclosure according to GRI standards of 360 enterprises in the period 2015-2019. The research results have revealed a positive relationship between SR and FV when measuring the SR by the aggregate indicator and components such as the general indicators, the economic dimension and the environmental and social dimensions. The research results suggest some recommendations to increase awareness and improve SR publication, which will help businesses add value.
Keywords: G32; Q56; 650; social responsibility; enterprise value; GRI; operational efficiency; Sustainability report